PVA Hydrogel Electrolyte and Porous Polyisoprene Carbon Nanostructure Composite Based Pressure Sensitive Supercapacitor - Lapčinskis, L.; Cirulis, I.; Abele, A.; Šutka, A.; Knite, M.; Lesničenoks, Pēteris (Institute of Physics Publishing, 2019)
Narrow operational voltage window can be considered as one of the greatest limitations for aqueous polymer electrolytes. Using freeze-thaw hydrogel preparation method we have synthesized wider potential window electrolytic polyvinyl alcohol (PVA)/Na2SO4 and PVA/K2SO4 electrolytes. Supercapacitors (SC) have been assembled using novel porous polyisoprene and carbon black composite electrodes. Our SC exhibit pressure sensitive properties therefore this effect is deeper explored here, giving explanation for capacitance increase during pressure application. It is found that up to 2 MPa the capacitance increases due to greater interface between electrode and electrolyte.
Special gratitude is in order to Raimonds Orlovs for temperature dependent resistance measurements. Financial support of project 1.1.1.1/16/A/013, “Hybrid energy harvesting systems” is greatly appreciated.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics